2021
DOI: 10.1111/mpp.13130
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of pathogenicity genes in rice sheath blight pathogen Rhizoctonia solani by a novel host‐induced gene silencing system

Abstract: Rice (Oryza sativa) is one of the most important cereal crops cultivated around the world. Rice cultivation often suffers from several types of diseases, including rice sheath blight (RSB), caused by the basidiomycete fungus Rhizoctonia solani. RSB is one of the most devastating rice fungal diseases globally and causes significant yield losses and reductions in rice grain quality (Moni et al., 2016;Rao et al., 2019;Wang et al., 2018). RSB often occurs under warm and humid conditions, particularly in tropical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In total, five fragments were prepared for HIGS vector construction ( Table 1 ). Using the “Gateway cloning system,” all were first cloned into the entry vector pDONR221 and then moved into the HIGS destination vector individually ( Zhao et al, 2021 ). After recombination cloning, each target fragment was inserted into two regions of the destination vector flanked by recombination sites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, five fragments were prepared for HIGS vector construction ( Table 1 ). Using the “Gateway cloning system,” all were first cloned into the entry vector pDONR221 and then moved into the HIGS destination vector individually ( Zhao et al, 2021 ). After recombination cloning, each target fragment was inserted into two regions of the destination vector flanked by recombination sites.…”
Section: Resultsmentioning
confidence: 99%
“…For HIGS expression, pBDL03 (gift from Dr. Shaohong Qu) was used as the destination vector ( Zhao et al, 2021 ). This vector is derived from the pANDA vector ( Okano et al, 2008 ) and designed so that each target fragment is inserted into two regions flanked by recombination sites in opposite directions, resulting in inverted repeat sequences linked by Gus gene (Fragments were separated by Gus linker, Gus linker sequence can be found on website 4 ), controlled by maize ( Zea mays ) ubiquitin promoter and T3A terminator ( Miki and Shimamoto, 2004 ; Okano et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the conserved SAM and RA domains in both ascomycetes and basidiomycetes, a broad spectrum of resistance against many plant fungal diseases caused by ascomycetous pathogens (e.g., rice blast pathogen Magnaporthe oryzea , cotton blight pathogen Verticillium dahlia , and sugarcane Pokkah boeng pathogen Fusarium species complex) and basidiomycetes pathogens (e.g., maize smut pathogen U. maydis , rice sheath blight pathogen Rhizoctonia solani , and sugarcane smut pathogen S. scitamineum ) could be developed by using host-induced gene silencing (HIGS) to target Ubc2 transcripts ( Hua et al, 2018 ; Koch and Wassenegger, 2021 ). In this regard, a current report showed that HIGS was highly efficient for developing transgenic lines in rice resistant to sheath blight caused by R. solani ( Zhao et al, 2021 ). In fact, recombinant microRNAs expressed by cotton plant could inhibit virulent gene expression in V. dahlia , and the transgenic plants showed elevated resistance to cotton blight ( Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%